Immunopathogenesis of Sarcoidosis and Risk of Malignancy: A Lost Truth?. (April 2013) - Tana, C.; Giamberardino, M.A.; Di Gioacchino, M.; Mezzetti, A.; Schiavone, C.
The hypothesis of a relationship between sarcoidosis and malignancy was firstly formulated in 1972 by Brincker. He documented an association of sarcoid reactions or sarcoidosis with 19 lymphomas and associated malignancies. Based on various epidemiological studies, for more than 20 years sarcoidosis has been considered as a condition at increased risk for cancer, particularly lymphoproliferative disorders. The existence of a sarcoidosis-lymphoma syndrome was therefore proposed, highlighting, as a potential mechanism, the uncontrolled lymphocyte proliferation and mitotic activity. A reduced ability to eliminate an antigen and chronic inflammation have been suggested as triggering events. Leading to a reduced tumor immune surveillance, a diminished myeloid dendritic cells (mDC) function, despite up-regulated co-stimulatory and maturation markers, was also raised as potential mechanism. However, some subsequent studies have questioned the presence of a close association between the two entities and have explained those previously published as the result of selection bias and misclassification. Recently, a Swedish population-based cohort study documented a significant overall excess incidence of cancer among sarcoidosis patients, especially those with multiple hospitalizations or admission in older age, emphasizing again a potential neoplastic risk. Therefore, currently, whether these patients have an increased risk of developing malignant lesions is still debated. Larger and unbiased studies are needed before drawing definite conclusions.